Induction and rejoining of DNA double-strand breaks in the lymphocytes of prostate cancer patients after radium-223 treatment as assessed by the γH2AX foci assay - Runge, Roswitha; Oehme, Liane; Grosche-Schlee, Sabine; Braune, Anja; Freudenberg, Robert; Kotzerke, Jörg (Nuklearmedizin - NuclearMedicine, 2019)
Aim The aim of this study is to assess if the number of radiation-induced double strand breaks (DSB) in lymphocytes of prostate cancer patients is affected after repeated Ra-223 therapies. In addition, we investigated the repair of ex vivo induced DSB to investigate the repair proficiency in patient’s lymphocytes over the therapy course.Methods Before each of six therapy cycles, blood samples were obtained from seventeen patients. After separation of lymphocytes, the cells were subjected to immunofluorescence staining for detection of DSB-marking γH2AX foci. The number of foci per cell per patient sample was determined for each cycle (X1-X6, baseline foci per cell). Additionally, appropriate samples were exposed ex vivo to an X-ray dose of 1 Gy. The number of γH2AX foci per cell were analyzed after 0.5 h, 2 h and 24 h of recovery.Results Patient-specific linear regression of the baseline foci per cell over the therapy cycles revealed no significant slopes in the regression lines. Likewise, the mean baseline foci per cell of all patients for cycles X2-X6 was not significantly elevated in comparison to the pre-therapeutic value (X1). The differences between the percentages of residual DSB and cycles were not significant, both at 2 h and 24 h repair time. Consideration of the X6/X1 ratios of both the number of lymphocytes and the amount of residual damage at 24 h indicated a significant correlation.Conclusion Our findings indicate that the number of γH2AX foci per cell was not changed in dependence on the Ra-223 therapy cycles. The ability of patient’s lymphocytes to repair ex vivo induced DSB remained unaffected throughout the entire therapy course.
Keywords: prostate carcinoma; bone metastases; Ra-223 treatment; double strand breaks; γH2AX foci